Design and construct a Yagi Antenna with Three Reflector Element to Strengthen 4G Signal in Rural Areas - Septima, Uzma; Nasrul; Firdaus; Uliana, Rafika (SOTVI, 2023)
Rural areas are indicated to be still difficult to reach by 4G signals due to diverse topographical conditions and uneven landscapes, especially hilly areas that weaken the signal reception level in this region. To make the 4G signal accessible in this area, a repeater in the form of an antenna is needed to strengthen the signal. In this study, a yagi antenna is designed with three reflector elements at a working frequency of 1800 Mhz 4G LTE, expected to produce a minimum gain of 12 dBi and a more focused antenna radiation to strengthen the 4G signal in rural areas. The antenna design was simulated using CST Studio Suite software, with optimized simulation results yielding a return loss of -22 dB, VSWR 1.167, and gain 12.40 dBi. From the measurements obtained, the yagi antenna with three reflector elements works well at a frequency of 1800 Mhz, with a return loss of -34.77 dB, VSWR 1.065, gain 12.96 dBi, and unidirectional radiation. With the optimal antenna parameters and the addition of three reflector elements, it's possible to increase the gain value, even though the gain increase isn't substantial, and it narrows the HPBW (Half Power BeamWidth) value. Moreover, testing the yagi antenna at 3 different distances demonstrated that the resulting gain value can enhance 4G signal speed in rural areas